Membrane Technology for the Recovery of Lignin: A Review - Humpert, D.; Ebrahimi, M.; Czermak, Peter (My University, 2016)
Utilization of renewable resources is becoming increasingly important, and only sustainable processes that convert such resources into useful products can achieve environmentally beneficial economic growth. Wastewater from the pulp and paper industry is an unutilized resource offering the potential to recover valuable products such as lignin, pigments, and water [1]. The recovery of lignin is particularly important because it has many applications, and membrane technology has been investigated as the basis of innovative recovery solutions. The concentration of lignin can be increased from 62 to 285 g.L-1 using membranes and the recovered lignin is extremely pure. Membrane technology is also scalable and adaptable to different waste liquors from the pulp and paper industry.
Citation: Humpert, D., Ebrahimi, M., & Czermak, P. (2016). Membrane Technology for the Recovery of Lignin: A Review. Membranes, 6(3), 13. doi:10.3390/membranes6030042
Keywords: Ceramic Membrane; Lignin Treatment; Lignin Fractionation; Lignosulfonate; Spent Sulfite Liquor; Spent Sulfite Liquor